Polymyxin B Resistance in El Tor Vibrio cholerae Requires Lipid Acylation Catalyzed by MsbB - Matson, Jyl S. (American Society for Microbiology (ASM), 2010)
Antimicrobial peptides are critical for innate antibacterial defense. Both Gram-negative and Gram-positive microbes have mechanisms to alter their surfaces and resist killing by antimicrobial peptides. In Vibrio cholerae, two natural epidemic biotypes, classical and El Tor, exhibit distinct phenotypes with respect to sensitivity to the peptide antibiotic polymyxin B: classical strains are sensitive and El Tor strains are relatively resistant. We carried out mutant screens of both biotypes, aiming to identify classical V. cholerae mutants resistant to polymyxin B and El Tor V. cholerae mutants sensitive to polymyxin B. Insertions in a gene annotated msbB (encoding a predicted lipid A secondary acyltransferase) answered both screens, implicating its activity in antimicrobial peptide resistance of V. cholerae. Analysis of a defined mutation in the El Tor biotype demonstrated that msbB is required for resistance to all antimicrobial peptides tested. Mutation of msbB in a classical strain resulted in reduced resistance to several antimicrobial peptides but in no significant change in resistance to polymyxin B. msbB mutants of both biotypes showed decreased colonization of infant mice, with a more pronounced defect observed for the El Tor mutant. Mass spectrometry analysis showed that lipid A of the msbB mutant for both biotypes was underacylated compared to lipid A of the wild-type isolates, confirming that MsbB is a functional acyltransferase in V. cholerae.